Supramolecular Polymerization of Supermacrocycles: Effect of Molecular Conformations on Kinetics and Morphology. Issue 22 (16th February 2017) - Yamauchi, Mitsuaki; Adhikari, Bimalendu; Prabhu, Deepak D.; Lin, Xu; Karatsu, Takashi; Ohba, Tomonori; Shimizu, Nobutaka; Takagi, Hideaki; Haruki, Rie; Adachi, Shin‐ichi; Kajitani, Takashi; Fukushima, Takanori; et al.
Abstract: Intricately designed π‐conjugated molecules containing interactive groups can be used to generate supramolecular polymers with outstanding structural and functional properties. To construct such supramolecular polymers, the non‐covalent synthesis of supermacrocyclic monomers from relatively simple molecules represents an attractive strategy, although this has been rarely exploited. Here, we report the supramolecular polymerization of two barbiturate‐naphthalene derivatives that circularly hexamerize by hydrogen bonding. The two molecules contain an aliphatic "wedge" unit with either an ether or ester linkage. This subtle difference is amplified into distinct features both in terms of the morphology of the supramolecular polymers and the polymerization process. The degrees of conformational freedom of the wedge unit determine the stacking of the supermacrocycles, as is evident from 2D X‐ray diffraction analyses on the aligned fibers. The differences in stacking impart the supramolecular polymer fibers with different morphological features (cylindrical or helical), which are reflected in the properties of concentrated solutions (suspension or gel). The degrees of conformational freedom of the wedge unit also affect the polymerization kinetics, in which the more flexible ether linkage induces pathway complexity by the formation of off‐pathway aggregates. Abstract : Big cycles, little details : Supramolecular polymerization of naphthalenes that hexamerized through hydrogen bonding is studied in detail. Distinct degrees of conformational freedom play important roles on kinetics and morphology.